Validation of a Mitotic Index Cutoff as a Prognostic Marker in Undifferentiated Uterine Sarcomas. (September 2017) - Hardell, Elin; Josefson, Sofia; Ghaderi, Mehran; Skeie-Jensen, Tone; Westbom-Fremer, Sofia; Cheek, Elizabeth H.; Bell, Debra; Selling, Jonas; Schoolmeester, John K.; Måsbäck, Anna; Davidson, Ben; Carlson, Joseph W.
Abstract : Undifferentiated uterine sarcomas (UUS) are a heterogenous group of high-grade mesenchymal tumors. Although these tumors are highly aggressive, a subset of patients may experience long-term survival. These tumors have previously been divided morphologically into uniform and pleomorphic types. A previous study demonstrated that a mitotic index cutoff of 25 mitoses/10 high-power fields (corresponding to 11.16 mitotic figures/mm 2 ) could successfully divide tumors into 2 prognostic groups with significantly different overall survival. The goals of the current study were to (1) validate this mitotic index cutoff in an independent, multicenter cohort and (2) explore the prognostic value of the mitotic index groups in relation to other clinicopathologic variables. Cases were included from 3 independent institutions: The Norwegian Radium Hospital, The Mayo Clinic, and Skåne University Hospital. A total of 40 tumors were included after central review. All cases were negative for the YWHAE-FAM22A/B and JAZF1-JJAZ1 translocations. Survival data were available on all patients. In this study, one-third of patients with UUS survived beyond 5 years. The crude (unadjusted) Cox Proportional Hazards model revealed a number of parameters that significantly impacted overall survival, including mitotic index group, patient age, stage, and the presence of tumor necrosis. Classification into the uniform and pleomorphic types was not prognostic. Combining these parameters into an adjusted model revealed that only the mitotic index group and stage were prognostic. On the basis of these findings, it is proposed that UUS be subdivided into "mitogenic" and "not otherwise specified" types.